Brexit in the Contemporary Novel - Hájková, Lucie (Univerzita Pardubice, 2022)
This bachelor thesis deals with the features of British identity influenced by Brexit and their projections in the works of Ian McEwan and James Silvester. The theoretical part outlines the background of Brexit and introduces the concepts of British identity, especially political tendencies, notion of lost empire and image of insularity. The practical part demonstrates how the authors interpret the influence of Brexit on these features and shows this perception in specific examples from the novels The Cockroach and Blood, White and Blue.
Brexit v současném románu
Keywords: Brexit; britská identita; politika; impérium; ostrovnost; Brexit; British identity; politics; empire; insularity